Is fisheries policy driving rural depopulation? Exploring how the implementation of the quota management system has affected rural settlement structures in Iceland - Víðisson, Magnús (UiT The Arctic University of Norway, 2020)
Iceland has been dependent on the ocean and the resources found within it for centuries. With greater technology and fishing effort in the past decades, overfishing had become a serious threat to the nation’s largest commercial stocks. This development led to restrictions on the fisheries which later led to the implementation of the ITQ system. Fisheries in Iceland are conducted with sustainability in mind but there have been general assumptions that the social dimension has not gained from Iceland’s current fisheries management system. As in, due to its structure it has led to depopulation within rural settlements. This study will examine if there is a link between the implementation of the quota management system in the 1980s and depopulation in rural settlements in Iceland. This study will examine how landing patterns and quota share developments have changed regionally and how it could be linked to changes in fisheries policies. And it will attempt to answer if these factors link when it comes to depopulation in rural settlements in Iceland. Keywords: Population development, ITQ, fisheries management, settlement structures, fisheries policy, depopulation, Iceland